PENERAPAN DIABETES SELF MANAGEMENT EDUCATION (DSME)DALAM MENINGKATKAN DIMENSI FISIK DAN PSIKOLOGIS KUALITAS HIDUP PASIEN DIABETES MELLITUS (DM) TIPE 2 DI RSUP DR. SOERADJI TIRTONEGORO KLATEN - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2015)
Diabetes mellitus (DM) is one of the most chronic diseases experienced by many people in the world. Diabetes Mellitus ranks fourth leading cause of death in the develop countries. Diabetes can cause to complications of acute and chronic complications. DSME is a process gives knowledge to patients about application of self care strategies independently to optimize metabolic control, prevent complications and improve the quality of life of patients with diabetes mellitus.The research was a qualitative with action research design that consisted of 3 cycles, each cycle consist of a plan, action, observation and reflection. Participants in this study are five people with type 2 diabetes who do outpatient at Dr. Soeradji Tirtonegoro Klaten Hospital were taken based on inclusion and exclusion criteria have been determined. Independent variables: application of Diabetes Self Management Education (DSME), while the dependent variable in this study is the physical and psychological dimensions of quality of life. The first cycle of checking the physical and psychological dimensions of quality of life before and then continued Diabetes Self Management Education. The second cycle of checking the physical dimensions of quality of life after Diabetes Self Management Education training. The third cycle of checking the psychological dimensions of quality of life after Diabetes Self Management Education    training. The results showed changes of quality of life in the physical and psychological dimensions after Diabetes Self Management Education (DSME) training. The changes in the physical dimension include increased of energy balance, increased of sleep activity, increased of physical activity, improved of physical comfort and increased of self health management. While changes in the psychological dimension among others include adaptive coping respons, positive feelings, decrease negative feeling, self acceptance, and an increase of religious spirituality. The conclusion of this study is there is an increase of quality of life in outpatients with type 2 diabetes at Dr. Soeradji Tirtonegoro Klaten Hospital after DSME training.